Isolation of the glycoside from the leaves of Lagerstroemia speciosa (Linne) Pers. Fam. Lythraceae (Banaba) - Racho, Angelito Celso Corsame
The isolation of glycosides from the leaves of Lagerstroemia speciosa (Linne) Pers. Fam. Lyrthraceae (locally known as banaba) was done first by a series of extraction using different solvents and second by thin layer chromatography of the different extracts.